2021
DOI: 10.1097/qai.0000000000002780
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hospitalization in People With HIV and COVID-19

Abstract: Each variable was added separately in the univariate models, and the variables that were found to be significantly associated with hospitalization (P , 0.05) in the univariate models were included in the multivariable models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…Similarly-among 2988 PLWH diagnosed with COVID-19 in New York State-the mortality rate was higher compared to those without HIV (standardized RR, 1.23 (95% CI, 1.07-1.40)) [33 [34], within the US TriNetX database [54], as well as in the Western Cape Province, South Africa (AHR 2.36; 95% CI: 1.47-3.78) [17] analysis. A similar risk profile for PLWH with lower CD4 counts was seen inn a multi-center registry of PLWH in the USA which included 286 hospitalized PLWH [55], in the University of Colorado Health System among 206 PLWH with COVID-19 [56], and in a health system cohort in San Francisco among 136 PLWH with COVID-19 [36]. Having a CD4 + T-cell count nadir < 200 cells/mm 3 was additionally associated with hospitalization in a multi-center cohort of PLWH in the USA which included 649 cases of COVID-19 (ARR 1.67; 95% CI 1.18-2.36) [57••].…”
Section: Risk Of Severe Covid-19 Among Plwh and Its Risk Factorsmentioning
confidence: 55%
“…Similarly-among 2988 PLWH diagnosed with COVID-19 in New York State-the mortality rate was higher compared to those without HIV (standardized RR, 1.23 (95% CI, 1.07-1.40)) [33 [34], within the US TriNetX database [54], as well as in the Western Cape Province, South Africa (AHR 2.36; 95% CI: 1.47-3.78) [17] analysis. A similar risk profile for PLWH with lower CD4 counts was seen inn a multi-center registry of PLWH in the USA which included 286 hospitalized PLWH [55], in the University of Colorado Health System among 206 PLWH with COVID-19 [56], and in a health system cohort in San Francisco among 136 PLWH with COVID-19 [36]. Having a CD4 + T-cell count nadir < 200 cells/mm 3 was additionally associated with hospitalization in a multi-center cohort of PLWH in the USA which included 649 cases of COVID-19 (ARR 1.67; 95% CI 1.18-2.36) [57••].…”
Section: Risk Of Severe Covid-19 Among Plwh and Its Risk Factorsmentioning
confidence: 55%
“…46 Our results demonstrate consistent and significant increased risk of hospitalization in PWH with lower CD4 counts, an association that has been confirmed in multiple global settings. 39,47–49 While most marked in PWH with CD4 counts <200 cells/mm 3 , risk of hospitalization was significantly elevated in people with CD4 counts <350 cells/mm 3 compared with those with CD4 counts ≥350 cells/mm 3 . In addition to current CD4 count, we also found that lowest CD4 count and lower current CD4/CD8 ratio were associated with an increased risk of hospitalization, suggesting an immune exhaustion effect persisting from the time of CD4 nadir despite subsequent CD4 reconstitution.…”
Section: Discussionmentioning
confidence: 98%
“…PLWDH who are in care may be more engaged in healthcare services and may be more likely to access the hospital than those not in care. In addition, PLWDH have a high prevalence of comorbidities that increase the risk of severe COVID-19 infection, [29][30][31][32][33] so it is plausible that PLWDH with comorbidities may be more engaged in the healthcare system in general and thus more likely to have access to hospitalization. This study did not assess COVID-19 diagnoses among all PLWDH, so we are unable to determine the extent to which SARS-CoV-2 infection varied by vaccination status.…”
Section: Discussionmentioning
confidence: 99%